Transcranial direct current stimulation (tDCS) in addition to walking training on walking, mobility, and reduction of falls in Parkinson’s disease: study protocol for a randomized clinical trial - Nascimento L.R. (2021)
© 2021, The Author(s).Background: Transcranial direct current stimulation (tDCS) has the potential to modulate cortical excitability and enhance the effects of walking training in people with Parkinson’s disease. This study will examine the efficacy of the addition of tDCS to a task-specific walking training to improve walking and mobility and to reduce falls in people with Parkinson’s disease. Methods: This is a two-arm, prospectively registered, randomized trial with concealed allocation, blinded assessors, participants and therapists, and intention-to-treat analysis. Twenty-four individuals with Parkinson’s disease, categorized as slow or intermediate walkers (walking speeds ≤ 1.0 m/s), will be recruited. The experimental group will undertake a 30-min walking training associated with tDCS, for 4 weeks. The control group will undertake the same walking training, but with sham-tDCS. The primary outcome will be comfortable walking speed. Secondary outcomes will include walking step length, walking cadence, walking confidence, mobility, freezing of gait, fear of falling, and falls. Outcomes will be collected by a researcher blinded to group allocation at baseline (week 0), after intervention (week 4), and 1 month beyond intervention (week 8). Discussion: tDCS associated with walking training may help improve walking of slow and intermediate walkers with Parkinson’s disease. If walking is enhanced, the benefits may be accompanied by better mobility and reduced fear of falling, and individuals may experience greater free-living physical activity at home and in the community. Trial registration: Brazilian Registry of Clinical Trials (ReBEC) RBR-6bvnx6. Registered on September 23, 2019